2017
DOI: 10.1016/j.pbb.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Differences between adolescents and adults in the acute effects of PCP and ketamine and in sensitization following intermittent administration

Abstract: Adolescence is a phase of development during which many physiological and behavioral changes occur, including increased novelty seeking and risk taking. In humans, this is reflected in experimentation with drugs. Research demonstrates that drug use that begins during adolescence is more likely to lead to addiction than drug use that begins later in life. Despite this, relatively little is known of the effects of drugs in adolescence, and differences in response between adolescents and adults. PCP and ketamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 98 publications
(143 reference statements)
3
18
0
Order By: Relevance
“…Locomotor sensitization due to glutamate antagonists is usually only observable soon after ketamine dosing, or subsequently to a challenge with another NMDAR blocker [12,20,23,40]. Our data are in accordance with former studies where no changes in total locomotion were observed 24 or 48 h after the last administration of ketamine [21,23].…”
Section: Discussionsupporting
confidence: 93%
“…Locomotor sensitization due to glutamate antagonists is usually only observable soon after ketamine dosing, or subsequently to a challenge with another NMDAR blocker [12,20,23,40]. Our data are in accordance with former studies where no changes in total locomotion were observed 24 or 48 h after the last administration of ketamine [21,23].…”
Section: Discussionsupporting
confidence: 93%
“…Abuse of NMDA antagonists in adolescence is associated with higher overall effect, risks for developing psychosis and dependence compared to adult use in human subjects. This notion was demonstrated in rats too ( Rocha et al, 2017 ) where adolescent rats displayed more pronounced behavioral activation to single dose of PCP and ketamine. Contrarily, repeated intermittent dosing of these drugs showed more pronounced sensitization effect in adults than in adolescent rats.…”
Section: Discussionmentioning
confidence: 85%
“…Juvenile male rats injected with an effective antidepressant dose of ketamine (20 mg/kg, i.p.) were more sensitive to its acute locomotor-activating effects as compared to adults ( Parise et al, 2013 ; Rocha et al, 2017 ). However, sensitization to the locomotor activating effects of ketamine occurred in both adolescent and adult male rats ( Rocha et al, 2017 ).…”
Section: The Addictive Potential Of Repeated Low-dose Ketamine Infusimentioning
confidence: 93%
“… Daily no change n/a (Wiley et al, 2007) 20 mg/kg i.p. Daily ↑ locomotor sensitization no change in CPP n/a ( Rocha et al, 2017 ) n/a ( Parise et al, 2013 ) Female Adolescent 10 mg/kg i.p. Daily ↑ locomotor sensitization n/a ( Wiley et al, 2011 ) (inf = infusion; i.p.…”
Section: The Addictive Potential Of Repeated Low-dose Ketamine Infusimentioning
confidence: 99%